Credit Risk Dynamics of Infrastructure Investment : Considerations for Financial Regulators - Jobst, Andreas A. (World Bank, Washington, DC, 2018)
Prudential regulation of infrastructure investment plays an important role in creating an enabling environment for mobilizing long-term finance from institutional investors, such as insurance companies, and, thus, gives critical support to sustainable development. Infrastructure projects are asset-intensive and generate predictable and stable cash flows over the long term, with low correlation to other assets; hence they provide a natural match for insurers' liabilities-driven investment strategies. The historical default experience of infrastructure debt suggests a "hump-shaped" credit risk profile, which converges to investment grade quality within a few years after financial close -- supported by a consistently high recovery rate with limited cross-country variation in non-accrual events. However, the resilient credit performance of infrastructure -- also in emerging market and developing economies -- is not reflected in the standardized approaches for credit risk in most regulatory frameworks. Capital charges would decline significantly for a differentiated regulatory treatment of infrastructure debt as a separate asset class. Supplementary analysis suggests that also banks would benefit from greater differentiation, but only over shorter risk horizons, encouraging a more efficient allocation of capital by shifting the supply of long-term funding to insurers.